Edukasi Bahaya Gadget bagi Anak Usia Dini dan Melatih Kecerdasan dengan Sarana Kreativitas Melukis Layangan - Erwin Barita Maniur Tambunan; Muhammad Abbas Adika; Awaludin Fahriyansyah; Winda Aulya; Zulham Ilyas; Farel Athaya Yulian; Alvaro Farrel Wijaya; Rislon Brayen Simatupang; Dwi Hardiyana Saputra; Syamil Ihsanuddin; Ali Akbar (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2026)
Technological advancements in the modern era have led to increased gadget usage across various age groups, including children. While gadgets facilitate learning, uncontrolled use carries potential negative consequences, such as addiction, reduced social interaction, and impaired psychological development. To address this, university students participating in the Community Service Program (KKN) conducted educational sessions and training for children in grades 1–6 of elementary school and grade 1 of junior high school. The program comprised three activities: an educational session on the risks of gadget use for children, an interactive word-guessing game, and a creative kite-painting session. The methods employed included face-to-face instruction using interactive videos and educational vocabulary cards, alongside kite painting to foster creativity. The results showed that participants actively engaged in discussions during the Q&A sessions regarding gadget usage. The word-guessing game revealed that most participants still required guidance in reading and comprehending English vocabulary, while the kite-painting activity demonstrated the children's high level of creativity through diverse artworks and their ability to explain the meanings behind their paintings. Observations indicated that the children maintained active social interactions, with almost no participants showing signs of gadget addiction or social withdrawal. This program provided education on the wise use of gadgets while simultaneously enhancing the children's creativity, social interaction, and cognitive skills through interactive learning activities.